Study of Molecular Complex Formation between Components, Chloroform and Arylamine in Methanol with dye Indicator Part-I - Farasram, Rakesh; Farasram, P.L.; Desai, C.M. (Asian Journal of Chemistry, 2010)
Molecular complex formation is possible in binary organicliquids due to different types of interactions as concluded by severalworkers by studying different physical properties. Hence it wasthought interesting to study the interaction between two organiccomponents, chloroform and arylamine, in polar solvent methanolspectrophotometric ally by monovariation method using dye indicatorcrystal violet and found that two types of molecular complexeswere formed in the stoichiometric ratios 1 : 1 and 1 : 2.